Novel insights in Erdheim-Chester disease using in vivo reflectance confocal microscopy - Pimenta, Rita (2021)
© 2020 by the American Academy of Dermatology, Inc. Published by Elsevier, Inc. This is an open access article under the CC-BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).